Additive Manufacturing of CoCrFeMnNi High‐Entropy Alloy/AISI 316L Stainless Steel Bimetallic Structures. Issue 7 (30th June 2022) - Sokkalingam, Rathinavelu; Chao, Zhao; Sivaprasad, Katakam; Muthupandi, Veerappan; Jayaraj, Jayamani; Ramasamy, Parthiban; Eckert, Jürgen; Prashanth, Konda Gokuldoss
Abstract : CoCrFeMnNi high‐entropy alloy (HEA)/AISI 316L stainless steel bimetals were additively fabricated using selective laser melting (SLM). The bimetal structure comprises three regions, i.e., CoCrFeMnNi‐HEA, AISI 316L stainless steel, and an interface between CoCrFeMnNi‐HEA, AISI 316L stainless steel. SLM processing results in the formation of columnar grains extending over many built layers epitaxially in a preferential <100> growth direction. The Vickers microhardness ranges mainly between 250 and 275 HV0.5 in all three observed regions. In addition, only a marginal variation in tensile strength is observed between the CoCrFeMnNi‐HEA, AISI 316L stainless steel, and the CoCrFeMnNi‐HEA/AISI 316L stainless steel bimetal. The unique higher work hardening behavior of the CoCrFeMnNi‐HEA prevents failure along the CoCrFeMnNi‐HEA side in the bimetallic structure during plastic deformation. The CoCrFeMnNi‐HEA shows higher pitting susceptibility than the AISI 316L stainless steel in the bimetallic structure due to its lower pitting potential. Further, the presence of pores and lack of fusion spots further decreases the pitting resistance of the CoCrFeMnNi‐HEA. Hence, the bimetal is prone to more preferential corrosion attack along the CoCrFeMnNi‐HEA side due to its anodic behavior and defects. Abstract : CoCrFeMnNi‐HEA/AISI316L stainless steel (SS) bimetal is successfully fabricated by selective laser melting (SLM). CoCrFeMnNi‐HEA is compatible with AISI316L‐SS as it shows epitaxial grain growth at the interface. Higher work hardening behavior prevents failure at CoCrFeMnNi‐HEA, even with similar mechanical properties like AISI316L‐SS during tensile loading of bimetal. Further, CoCrFeMnNi‐HEA shows more pitting corrosion due to lower pitting potential.